Desentralisasi Fiskal dan Pertumbuhan Ekonomi di Indonesia Apakah Desentralisasi Fiskal Memberikan Dampak yang Signifikan? - , RADITYO PUTUMAYOR ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The implementation of fiscal decentralization due the regional autonomy policy in Indonesia has been started since the early 2000s. It aims to provide optimal services to the citizen and reduce fiscal disparities among regions and between the central government with local governments. Each year the central government transferring the funds from the state budget to local governments up to 30% of the total state budget. The transfer and the local revenue become the major source of local budget. In the implementation of fiscal decentralization in Indonesia, yet significant portion of local revenue to fund the budget so that local governments still rely on transfers from the central government. Based on the literature and empirical studies, fiscal decentralization can make impacts on economic growth in both positive and negative. This study will analyze the impact of fiscal decentralization on economic growth (as a proxy of economic development) using a panel data with the Fixed Effect Model as the tool of analysis. The samples were 457 districts/cities in Indonesia with a span of years 2009-2011. The results show that fiscal decentralization has no effect on economic growth. Implementation of fiscal decentralization could have a positive impact on economic growth on average and greater in the regions with smaller local revenue than the regions that have a larger local revenue. This is possible because regions with a smaller local revenue receive funds transfers from the central government of a relatively larger amounts.